2012
DOI: 10.1287/mnsc.1110.1378
|View full text |Cite
|
Sign up to set email alerts
|

Do Cultural Differences Between Contracting Parties Matter? Evidence from Syndicated Bank Loans

Abstract: W e investigate whether cultural differences between professional decision makers affect financial contracts in a large data set of international syndicated bank loans. We find that more culturally distant lead banks offer borrowers smaller loans at a higher interest rate and are more likely to require third-party guarantees. These effects do not disappear following repeated interaction between borrower and lender and are economically sizable: A one-standard-deviation increase in cultural distance, approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(204 citation statements)
references
References 43 publications
8
195
1
Order By: Relevance
“…8 See for instance, Giannetti and Laeven (2012), Giannetti and Yafeh (2012). Saunders and Steffen (2011) use Dealscan data to investigate loan spread differences between public and private firms in the UK.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…8 See for instance, Giannetti and Laeven (2012), Giannetti and Yafeh (2012). Saunders and Steffen (2011) use Dealscan data to investigate loan spread differences between public and private firms in the UK.…”
Section: Datamentioning
confidence: 99%
“…syndicated loan market structure (Esty and Megginson (2004); Giannetti and Laeven (2012); Giannetti and Yafeh (2012)). …”
mentioning
confidence: 99%
“…Results in Panel C indicated that failing to account for time since entry or since becoming foreign owned, may confound comparisons between branches and subsidiaries. In Panel C we 44 See, among others, Bruno and Hauswald (2014), Claessens and van Horen (2014), Giannetti and Yafeh (2012), Gormley (2014), andMian (2006). 45 The literature also suggests that branches and subsidiaries follow different business models.…”
Section: What Drives Distance-related Information Constraints?mentioning
confidence: 99%
“…Such a cost can also be psychological. Starting with the seminal work of Becker (1957) on taste-based discrimination, numerous researches have found that mistrust, animosity and negative attitude across cultural groups have significant impact on trade and investment (Guiso et al, 2009, Michaels and Zhi, 2010, Fisman et al, 2014; on labor market outcomes (Becker, 1993, Bertrand and Mullainathan, 2004, Bandiera et al, 2009); on financial activities such as mergers and bank loans (Giannetti andYafeh, 2012, Ahern et al, 2012). We call the cost/disutility of cross-cultural interaction cultural aversion in the rest of the paper.…”
Section: Introductionmentioning
confidence: 99%